Treatment features of adult patients with acute myeloid leukemia during the COVID-19 pandemic - D. E. Gagloeva; E. N. Misyurina; T. N. Tolstykh; E. A. Baryakh; K. V. Yatskov; E. A. Karimova; A. B. Makeshova; M. A. Mingalimov; T. S. Chudnova; D. D. Ivanova; A. I. Koneva; O. L. Kochneva; et al. (Онкогематология)
Background. Acute myeloid leukemia (AML) is a highly aggressive oncological disease of the blood and bone marrow, requiring extremely toxic chemotherapy and massive supportive treatment to achieve stable remission. Currently, there is no work to provide medical care to these patients with a high risk of coronavirus infection. This paper presents treatment results of a large AML patient cohort during the COVID-19 pandemic.Aim. To assess the clinical features of coronavirus infection in AML patients.Materials and methods. A retrospective cohort study included patients hospitalized at City Clinical Hospital No. 52 (Moscow) between March 2020 and March 2022. Study inclusion criteria: 1) AML diagnosed within the last 3 years before the development of the COVID-19 pandemic; 2) age over 18 years; 3) laboratory confirmed SARS-CoV-2. AML status (newly diagnosed AML, relapse/refractory disease, remission), age, gender, comorbidity index, previous AML therapy and its outcomes were also assessed.Results. Among 218 patients with acute leukemia, 60 (27.5 %) patients had acute lymphoid leukemia, 158 (72.5 %) had AML. Patients with acute promyelocytic leukemia were allocated to a separate group - 20 (9 %) patients. The statistical data of the remaining 138 (63.5 %) patients with AML, their survival and mortality rates were assessed, and the main prognostic factors influencing the mortality and severity of coronavirus infection were identified. Also, our own results were compared with world statistics.Conclusion. Coronavirus infection in AML patients significantly worsens the prognosis. The main factors influencing the severity of coronavirus infection and survival and mortality rates are age, somatic status of patients due to the presence of concomitant chronic diseases, the development of deep hypoplasia of hematopoiesis, and the active AML status (disease onset or resistant course).